Enhancing Mental Health, Well-Being and Active Lifestyles of University Students by Means of Physical Activity and Exercise Research Programs - Herbert, Cornelia (Frontiers in Public Health, 2022)
Mental disorders (e.g., depression) and sedentary behavior are increasing, also among emerging adults. One particular target group of emerging adults with high sitting times and vulnerable to mental disorders are university students. In particular, anxiety and depressive symptoms as well as stress symptoms are very common among university students. The present manuscript discusses whether physical activity and exercise interventions constitute an important means of promoting mental health among emerging adults such as university students. First, current scientific evidence will be summarized, and based on this evidence, a university-based scientific research project will be introduced that investigates if physical activity, exercise interventions and acute bouts of exercise of low- to moderate intensity can buffer perceived stress, alleviate mental health conditions and strengthen wellbeing (psychologically and physiologically) among university students by positively influencing depressive and anxiety symptoms, perceived stress and emotion perception, body awareness and subjective wellbeing including overall quality of life. The research project, its concept, multimethod approach, and first results from available studies are discussed in relation to current scientific evidence, health care needs and future developments. The results from the studies conducted within the research project so far and that are briefly summarized in this manuscript suggest that physical activity, mental health and wellbeing are positively related, also in university students as an important group of emerging adults. The results further suggest that exercise interventions comprising aerobic exercises of low- to moderate intensity may work best to improve mental health (alleviate depressive symptoms and perceived stress) among university students after a few weeks of intervention. In addition, acute bouts of certain types of exercises (yoga in particular) seem to be particularly effective in changing perception of bodily signals, cardiac activity and emotion processing immediately after the exercise. The results underscore the importance of systematic investigations of the combined examination of psychological and physiological factors that promote an active lifestyle and at the same time strengthen mental health and wellbeing (psychologically and physiologically) among emerging adults such as university students.